2020
DOI: 10.1002/jgc4.1320
|View full text |Cite
|
Sign up to set email alerts
|

Pursuing genetic testing for children with autism spectrum disorders: What do parents think?

Abstract: The American Academy of Pediatrics, the American College of Medical Genetics and Genomics, and the American Academy of Neurology recommend genetic testing, as a genetic evaluation tool, for children diagnosed with autism spectrum disorders (ASD). Despite the potential benefits, the utilization of genetic testing is low. We proposed an integrated theoretical framework to examine parents’ intention and associated psychosocial factors in pursuing genetic testing for their children with ASD. Recruiting primarily f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 81 publications
3
3
0
Order By: Relevance
“…The results of this study suggest that parents of children with ASD in Taiwan generally hold favorable attitudes toward genetic testing for ASD, but they showed deficient knowledge of such testing. This finding is consistent with previous studies exploring parents’ attitudes and knowledge toward ASD genetic testing in the United States and Europe [ 27 , 28 , 29 , 30 , 31 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The results of this study suggest that parents of children with ASD in Taiwan generally hold favorable attitudes toward genetic testing for ASD, but they showed deficient knowledge of such testing. This finding is consistent with previous studies exploring parents’ attitudes and knowledge toward ASD genetic testing in the United States and Europe [ 27 , 28 , 29 , 30 , 31 ].…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, similar to other survey research, we were unable to obtain a 100% response rate and study the entire target population [ 54 ]. Thus, the findings of this study may not be generalized to all Taiwanese parents of children with ASD as a lack of generalizability is the most common limitation for survey studies [ 27 , 30 , 49 ]. Second, although the present study examined many sociodemographic characteristics’ associations with parental attitudes and knowledge of ASD genetic testing, other factors (e.g., culture, social norms, as well as perceived benefits and barriers) may still need to be explored to gain a more comprehensive picture of parents’ perspectives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that despite the availability of ASD genetic testing in Taiwan, nearly 50% of the parents of children with ASD in our sample were unaware of the availability of genetic testing for their children. Such findings have also been observed in other studies [ 17 , 18 , 36 , 37 ]. For example, Chen et al, [ 17 ] interviewed 42 Texas parents of children with ASD, and found that 63% of those parents had never heard of ASD genetic testing.…”
Section: Discussionsupporting
confidence: 90%
“…Understanding Taiwanese parental awareness and perceptions about genetic testing is crucial. Consistent with past research [ 17 , 18 , 36 , 37 ], this first-of-its-kind study (to the best of our knowledge) found that nearly half of the participants were unaware that genetic testing was an option for their child with ASD, which highlights an area that both healthcare agencies and ASD advocacy groups in Taiwan should seek to remedy. With approximately three-quarters of the participants responding favorably to the idea of ASD genetic testing for their children with ASD, making parents of children with ASD more aware of the genetic testing options available to them is very important.…”
Section: Discussionsupporting
confidence: 87%